2019
DOI: 10.1039/c9ra03623g
|View full text |Cite
|
Sign up to set email alerts
|

Separating graphene quantum dots by lateral size through gel column chromatography

Abstract: GQDs prepared through a photo-Fenton reaction were separated into eight groups with different sizes and fluorescent colors via gel column chromatography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…The UV–Vis absorption spectra shape become steeper and steeper from GQDs‐orange to GQDs‐blue. The fluorescence quantum yields (QYs) of GQDs‐orange, GQDs‐green, and GQDs‐blue are 0.758%, 5.905%, and 0.259%, respectively, as described in our previous work …”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…The UV–Vis absorption spectra shape become steeper and steeper from GQDs‐orange to GQDs‐blue. The fluorescence quantum yields (QYs) of GQDs‐orange, GQDs‐green, and GQDs‐blue are 0.758%, 5.905%, and 0.259%, respectively, as described in our previous work …”
Section: Resultsmentioning
confidence: 54%
“…The dialysis bag of 100–500 Da (retained molecular weight) was used for the purification of as‐prepared GQDs. Different sizes of GQDs were separated from the as‐prepared GQDs with the method of Sephadex G‐25 gel column chromatography as described in our previous work . Briefly, 4 mL of the as‐prepared GQDs aqueous suspension with a concentration of 2 mg mL −1 was added into the top of Sephadex G‐25 gel column.…”
Section: Methodsmentioning
confidence: 99%
“…However, this giant solvatochromism is hardly observed in the C-dot solution (Figure 7c,d). Figure 7e,f summarizes the PL peak position and QY as a function of E T (30), an indicator of solvent polarity. 57 With an increase of E T (30), the peak position of ECNO redshifts greatly but that of the C-dot solution shows no significant change.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Although carbon dots (C-dots) have found wide applications in various fields ranging from energy conversion to bioanalytics, their complex structures and insufficient purification have frequently led to misleading conclusions in reported studies. Increasing research studies have revealed that the photoluminescence (PL) of C-dots obtained from bottom-up routes is associated with versatile emission species: fluorophores, supramolecules or molecular aggregates, polymers, quasi-carbon dots, confined graphene fragments, and carbogenic nanoparticles. ,, These species can be roughly divided into two categories: molecular fluorophores that are akin to organic dyes and carbogenic nanodots bearing crystalline or amorphous phase of carbon. , In recent years, many types of molecular fluorophores have been separated and identified as single fluorescence origins inside carbon dots, such as citrazinic acid, 2-pyridine compounds, , pyrrolo­[3,4- c ]­pyridine, methylenesuccinic acid, thiazolo­[3,2- a ]­pyridine, etc. Compared with its carbogenic counterpart, the fluorophore-dominated fluorescence is frequently characterized as possessing excitation independence, high fluorescence quantum yield (QY), single fluorescence lifetime, and environmental sensitivity. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation